2014
DOI: 10.1155/2014/832989
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Gasification of Biomass in an Updraft Gasifier with External Recirculation of Pyrolysis Gases

Abstract: The updraft gasifier is a simple type of reactor for the gasification of biomass that is easy to operate and has high conversion efficiency, although it produces high levels of tar. This study attempts to observe the performance of a modified updraft gasifier. A modified updraft gasifier that recirculates the pyrolysis gases from drying zone back to the combustion zone and gas outlet at reduction zone was used. In this study, the level of pyrolysis gases that returned to the combustion zone was varied, and as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 17 publications
2
7
0
Order By: Relevance
“…Modeling starts with the approach to the process of experiments that have been carried out by Surjosatyo et al [4] as shown in Figure 1. Furthermore, the approaches are used to facilitate the simulation process.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Modeling starts with the approach to the process of experiments that have been carried out by Surjosatyo et al [4] as shown in Figure 1. Furthermore, the approaches are used to facilitate the simulation process.…”
Section: Methodsmentioning
confidence: 99%
“…The updraft gasifier has many advantages but, on the other hand, produced high level of tar [1]. Several modifications to gasifier with recirculation of pyrolysis gas have been conducted to reduce the tar [2][3][4]. In previous study, we have modified type of updraft gasifier with pyrolysis gas recirculated externally to the combustion zone.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this experiment, a reactor design with low tar content and high efficiency gas was obtained by adjusting the exit position of producer gas from the gasifier (Surjosatyo et al, 2014). Another experiment was conducted in Plered, Purwakarta using coconut shell, wood and rice husk as fuel.…”
Section: Introductionmentioning
confidence: 99%